2021
DOI: 10.1111/chso.12450
|View full text |Cite
|
Sign up to set email alerts
|

Turning 18 in specialised residential therapeutic care: Independence or a cliff edge?

Abstract: This article describes research undertaken in 2018 in a therapeutic residential home for young women with multiple and complex needs in out‐of‐home care in England. Based on qualitative interviews with five young women, aged 16–18, and four professionals working with the home, the article analyses the under‐researched leaving care needs and experiences of this group of young women. The findings highlight the tensions between notions of childhood and expectations of adulthood surrounding this group of young peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…Research has noted a lack of support for 'looked after' young people after the age of eighteen (Field, et al, 2021;Stein, 2012;Woodgate et al, 2017) and our study confirmed this to be the case for those attending university (Ellis & Johnston, 2020). Forty-one percent of survey respondents were no longer in touch with their carers by the time they prepared to move to university and over a quarter described their biggest champion as either 'myself' or 'no one'.…”
Section: Moving To University Without Supportsupporting
confidence: 70%
“…Research has noted a lack of support for 'looked after' young people after the age of eighteen (Field, et al, 2021;Stein, 2012;Woodgate et al, 2017) and our study confirmed this to be the case for those attending university (Ellis & Johnston, 2020). Forty-one percent of survey respondents were no longer in touch with their carers by the time they prepared to move to university and over a quarter described their biggest champion as either 'myself' or 'no one'.…”
Section: Moving To University Without Supportsupporting
confidence: 70%
“…In each example, the texts emphasised how extended care could contribute to improved engagement in education, employment and training, and reduce the risk of homelessness. Throughout these articles, young people and their carers described the experience of extended support as providing a valued service that could help alleviate the distress and anxiety during their transition from 'care' to independent living (Brisson et al, 2022;Curry & Abrams, 2015;Field et al, 2021).…”
Section: Extended Carementioning
confidence: 99%
“…Esta falta de apoyo ha sido evaluada y constatada como origen de una serie de dificultades en los procesos de transición que se han intentado suplir con nuevas medidas de apoyo adicionales denominadas "atención prolongada" o "atención extendida" que posibilitan pasar de un proceso de transición tumultuoso a uno más gradual. Con todo, la literatura evidencia una falta de consenso sobre estos apoyos (Bengtsson et al, 2018;Field et al, 2021;Keller et al, 2021;Schofield et al, 2017;Van Breda et al, 2020).…”
Section: Conceptualización De La Transiciónunclassified
“…Según Field et al (2021) tanto el término "transición" como el de "independencia" pueden generar sentimientos negativos de soledad y abandono. Barmen y Kiik (2019) instan a repensar las dicotomías en las que concebimos a los menores de edad como seres totalmente dependientes frente a personas adultas como independientes.…”
Section: Conceptualización De La Transiciónunclassified